The effect of a chin-down maneuver after esophagectomy on oropharyngeal swallowing pressure measured using high-resolution manometry. Issue 1 (February 2020) - Matsubara, Keigo; Kumai, Yoshihiko; Miyamoto, Takumi; Samejima, Yasuhiro; Yoshida, Naoya; Baba, Hideo; Orita, Yorihisa
Abstract: Objective: To elucidate the effects of a chin-down maneuver using high-resolution manometry (HRM) to measure pharyngeal swallowing pressure (SP) after esophagectomy. Methods: We evaluated 9 of 16 patients who underwent esophagectomy featuring gastric tube reconstruction and three-field lymph node dissection (3FL) in our Department of Gastroenterological Surgery from September 2015 to June 2016. We compared all parameters of the neutral and chin-down positions using HRM to measure the maximum SP at the velopharynx, meso-hypopharynx, and upper esophageal sphincter (UES) and the duration of lowered SP at the UES, the distance from nostrils to the boundary between hypopharynx and UES and to derive SP and SP propagation curves at various distances from the nostrils. Results: Compared to that at the neutral position, the maximum SP at the velopharynx was significantly lower in the chin-down position (p < 0.05); however, SP at the meso-hypopharynx and UES did not differ significantly. The duration of lowered SP at the UES was significantly prolonged in the chin-down position and the distance from nostrils to the boundary between hypopharynx and UES was significantly shortened representing the elevation of the larynx, respectively (p < 0.05, p < 0.01). On the SP propagation curve for males, the times to SP peaks at 13, 16, 17, and 18 cm from the nostrils were significantly prolonged (all p < 0.05) in the chin-down position. Conclusion: Chin-down positioning after esophagectomy/3FL may improve bolus passage by prolonging the duration of lowered SP at the UES, possibly by enhancing laryngeal elevation.